The mothers [compact disc, unabridged] : a novel - Bennett, Brit (Penguin Audio : Books on Tape, 2016)
"A dazzling debut novel from an exciting new voice, The Mothers is a surprising story about young love, a big secret in a small community--and the things that ultimately haunt us most. Set within a contemporary black community in Southern California, Brit Bennett's mesmerizing first novel is an emotionally perceptive story about community, love, and ambition. It begins with a secret. "All good secrets have a taste before you tell them, and if we'd taken a moment to swish this one around our mouths, we might have noticed the sourness of an unripe secret, plucked too soon, stolen and passed around before its season." It is the last season of high school life for Nadia Turner, a rebellious, grief-stricken, seventeen-year-old beauty. Mourning her own mother's recent suicide, she takes up with the local pastor's son. Luke Sheppard is twenty-one, a former football star whose injury has reduced him to waiting tables at a diner. They are young; it's not serious. But the pregnancy that results from this teen romance--and the subsequent cover-up--will have an impact that goes far beyond their youth. As Nadia hides her secret from everyone, including Aubrey, her God-fearing best friend, the years move quickly. Soon, Nadia, Luke, and Aubrey are full-fledged adults and still living in debt to the choices they made that one seaside summer, caught in a love triangle they must carefully maneuver, and dogged by the constant, nagging question: What if they had chosen differently? The possibilities of the road not taken are a relentless haunt. In entrancing, lyrical prose, The Mothers asks whether a "what if" can be more powerful than an experience itself. If, as time passes, we must always live in servitude to the decisions of our younger selves, to the communities that have parented us, and to the decisions we make that shape our lives forever"--